Evaluation of Public Finance in the Tourism Sector at the Municipal Budget Level - Plzáková, Lucie (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The Assessment of public finance in the context of their allocation function is usually defined by criteria called. 3E: economy, efficiency and effectiveness. This approach is used for analyses of public finance at the municipal level from the point of view of revenues from local taxes in direct connection with tourism and expenditures invested into tourism sector on the other hand. There is a total of 6,252 municipalities in the Czech Republic (2015). 903 municipalities (14.4 %) applied a local spa or recreational stay fee and 1,387 municipalities (22.2 %) applied local accommodation capacity fee in 2015. Municipalities gained 6.8 bn. CZK from both local fees during the reporting period 2000 – 2015. Prague, the capital city, holds a dominant position as far as the volume of financial means drawn through these fees is concerned. Investments into tourism development is much lower on the local level. The article aims to evaluate utilization of public finances in the tourism sector on local budget levels in the Czech Republic. A time series analysis, Pearson correlation coefficient, index analysis and comparison were used to achieve the goal. The primary and secondary data were subjected to the analysis
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 343-354
Keywords: 3E; local fees; tourism; municipalities; public finance